Las estrategias metodológicas y su incidencia en la lecto escritura, en los estudiantes de quinto grado de la Escuela de Educación Básica Juan León Mera; del Cantón Montalvo Provincia Los Ríos en el periodo lectivo 2023 – 2024 - Rodríguez Gavilanes, Geomara Alexandra (2023)
This research has been carried out with the purpose of determining the problems of reading and writing. This study makes it possible to overcome the learning problems that occur with students with low academic performance, allowing them to feel motivated and secure in the development of the educational process. Education must develop the processes of reading and writing to train new generations by forming critical, purposeful and reflective students who can function and develop meaningful learning to be better in the social and cultural sphere. Teachers are capable of training people who can understand when they read and understand what they write and thus achieve students with a good level of reading and spelling, thinking about the future of our students so that they achieve their goals and can function in a social environment. and every day be better. Reading is one of our best allies to achieve student development, so different methodologies must be applied so that the student learns in a different way.